1990
DOI: 10.1259/0007-1285-63-756-934
|View full text |Cite
|
Sign up to set email alerts
|

Real-time digital contrast enhancement and magnification in the assessment of scaphoid and other wrist injuries

Abstract: A study on the value of a commercially available desk-top digital magnifier-contrast enhancer (DETECT System) was made in a series of 550 patients presenting with an acute wrist injury. Four radiologists, of varying experience, independently reviewed the radiographs on a conventional lightbox and later with the digitizer. In the scaphoid series (350 cases), the performance of the two more experienced radiologists was marginally better with the digitizer, whereas the less experienced radiologists performed slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…42 Five studies also reported interrater kappa values for x-ray between radiologists and hand surgeons. [55][56][57][58][59] Several studies reported on x-ray imaging techniques that are not readily available in the ED, including carpal box x-rays, 60,61 digital contrast enhancement, 62 and dual x-ray absorption. 63 Waeckerle 42 reported that the initial x-ray sensitivity was 80% with 100% specificity (LR+ = infinity, LR-= 0.20).…”
Section: Radiographymentioning
confidence: 99%
“…42 Five studies also reported interrater kappa values for x-ray between radiologists and hand surgeons. [55][56][57][58][59] Several studies reported on x-ray imaging techniques that are not readily available in the ED, including carpal box x-rays, 60,61 digital contrast enhancement, 62 and dual x-ray absorption. 63 Waeckerle 42 reported that the initial x-ray sensitivity was 80% with 100% specificity (LR+ = infinity, LR-= 0.20).…”
Section: Radiographymentioning
confidence: 99%
“…Radiography is a cheap and widely used primary imaging technique in the diagnosis of clinically suspected scaphoid fractures (3, 7, 9, 20, 22). However, several reports conclude that initial and follow‐up conventional radiographs are not reliable for the detection of scaphoid fractures (22, 24).…”
mentioning
confidence: 99%
“…Radiography is a cheap and widely used primary imaging technique in the diagnosis of clinically suspected scaphoid fractures (3,7,9,20,22). However, several reports conclude that initial and follow-up conventional radiographs are not reliable for the detection of scaphoid fractures (22,24).…”
mentioning
confidence: 99%